Determining Factors for Stress Perception Assessed with the Perceived Stress Scale (PSS-4) in Spanish and Other European Samples - Vallejo, Miguel A.; Vallejo-Slocker, Laura; Fernández-Abascal, Enrique G.; Mañanes, Guillermo (Frontiers in Psychology, 2018)
Objective: Stress perception depends on cultural and social aspects that vary from one country to another. One of the most widely disseminated methods of assessing psychological stress is the Perceived Stress Scale (PSS-4). Therefore, in order to identify these factors and their impact on mental health, the present study compares the PSS-4 results among three European countries (Great Britain, France and Spain). This study focuses on PSS-4 results within a Spanish sample to determine: (1) normative data, reliability and validity of PSS-4 in a Spanish sample and (2) how stress perception changes depending on cultural and social factors. Methods: The data were obtained from a website representing a service of a smoking cessation program, the study represented a service that was open to all individuals. The number of participants were 37,451. They reported their age, gender, nationality, marital status, education and employment status, and completed two psychological questionnaires (PPS-4 and the anxiety and depression scales of the Symptom Checklist-90-Revised). Results: The PSS-4 scores could differentiate between relevant sociodemographic variables (such as sex, age, nationality, marital status, education, parental status, employment status, and income class). The PSS-4 scores showed a positive correlation with the SCL90R anxiety and depression scales. The normed values for interpreting the PSS-4 scores are presented. The PSS-4 showed adequate internal consistency and reliability. Conclusions: The PSS-4 is a useful instrument for assessing stress perception levels in the general population in different countries. Its internal consistency is sufficient for a 4-item scale.